Unlocking the Potential of Edible Malay Herbs by using Fourier-Transformed Infrared Spectroscopy Approach - Aqilah Qairina Mohd Helmi; Nurin Amelyn Imani Aznil Hisham; Muhammad Faris Zafran Mohd Farahan; Ehwan Ngadi (Kolej PERMATA Insan, 2025)
5th Insan Junior Researchers International Conference 2024 (iJURECON 2024) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Ahmad Bazli Ahmad Hilmi, Nurhidaya Mohamad Jan, Norazlina Subani 25-26 October 2024 Organized by : Kolej Permata Insan